2023
DOI: 10.1017/jfm.2023.237
|View full text |Cite
|
Sign up to set email alerts
|

Non-iterative vortex-based smearing correction for the actuator line method

Abstract: The actuator line method (ALM) is used extensively in wind turbine and rotor simulations. However, its original uncorrected formulation overestimates the forces near the tip of the blades and does not reproduce well forces on translating wings. The recently proposed vortex-based smearing correction for the ALM is a correction based on physical and mathematical properties of the simulation that allows for a more accurate and general ALM. So far, to correct the forces on the blades, the smearing correction depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, this accuracy is often questioned, especially at the blade tip, mostly due to the regularization of the forces that reduces the induced velocity. To mitigate this issue, it is either possible to use tip corrections (see (Dag and Sørensen, 2020;Meyer Forsting et al, 2019;Martínez-Tossas and Meneveau, 2019;Kleine et al, 2023)) or to use regularization kernels that lead to a more accurate prediction of the forces (Caprace et al, 2019;Jha and Schmitz, 2018). The second approach is used here, by using the 2D Gaussian regularization for both the evaluation of the effective velocity and the forces distribution.…”
Section: Actuator Line Methods (Alm)mentioning
confidence: 99%
“…However, this accuracy is often questioned, especially at the blade tip, mostly due to the regularization of the forces that reduces the induced velocity. To mitigate this issue, it is either possible to use tip corrections (see (Dag and Sørensen, 2020;Meyer Forsting et al, 2019;Martínez-Tossas and Meneveau, 2019;Kleine et al, 2023)) or to use regularization kernels that lead to a more accurate prediction of the forces (Caprace et al, 2019;Jha and Schmitz, 2018). The second approach is used here, by using the 2D Gaussian regularization for both the evaluation of the effective velocity and the forces distribution.…”
Section: Actuator Line Methods (Alm)mentioning
confidence: 99%
“…The subfilter-scale velocity correction presented in Martínez-Tossas and Meneveau 10 and shortly introduced in Section 1.3 can also be seen as a variant of a vortexbased correction. Kleine et al 17 observed that these methodologies introduce an error dependent on the difference of circulation between time steps and on the weighting/relaxation factors used.…”
Section: Shives and Crawfordmentioning
confidence: 99%
“…However, it may exhibit numerical instability near the blade tip and present difficulties when extending to the ADM. Although vortex-based correction has recently been devised [17], its demanding assumptions and intricate computing techniques make it unsuitable for extension to rotor computations. Additionally, a filtered ALM [18] was first used in fixed-wing applications and has been expanded to wind turbine simulations, using a finite difference methodology.…”
Section: Introductionmentioning
confidence: 99%